2019
DOI: 10.1002/nau.24175
|View full text |Cite
|
Sign up to set email alerts
|

Add‐on effects of tadalafil in tamsulosin‐treated patients with small benign prostatic enlargement: A randomized, placebo‐controlled, double‐blind, crossover study

Abstract: Aim: To assess the add-on effects of tadalafil in patients with a relatively small benign prostatic enlargement (BPE) treated with tamsulosin. Methods: From September 2014 to July 2018, we prospectively studied patients (aged 50 years or more) attending our hospital who had received tamsulosin for small BPE (20-40 mL) for 4 weeks at least and still had residual lower urinary tract symptoms (LUTS) with total International Prostate Symptom Scores (IPSS) of at least 8 and IPSS-quality of life scores at least 3. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Even in this A‐group, tadalafil significantly improved both the LUTS severity and bother. This add‐on effect of tadalafil in patients with residual LUTS after treatment with alpha‐blockers was consistent with previous reports 20,21 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even in this A‐group, tadalafil significantly improved both the LUTS severity and bother. This add‐on effect of tadalafil in patients with residual LUTS after treatment with alpha‐blockers was consistent with previous reports 20,21 …”
Section: Discussionsupporting
confidence: 92%
“…This add-on effect of tadalafil in patients with residual LUTS after treatment with alpha-blockers was consistent with previous reports. 20,21 Phosphodiesterase five inhibitors, including tadalafil, have been widely used for the treatment of erectile dysfunction. In the present study, the m-IIEF5 score did not significantly improve after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of nobiletin was seen after 6 weeks of administration in the previous report [13], so that was the time period used. In addition, many studies of lower urinary tract symptoms have shown significant efficacy at 6 weeks [28,29]. However, since there were no significant differences in the main efficacy item in the present study, it could be possible that the effect may be better recognized at 12 weeks, as reported by Yamada S. et al [12].…”
Section: Discussionsupporting
confidence: 42%
“…Through reading the full text, we excluded 30 articles due to the lack of useful information. Finally, six articles ( Bechara et al, 2008 ; Karami et al., 2016 ; Nagasubramanian et al, 2020 ; Negoro et al, 2020 ; Regadas et al, 2013 ; Singh et al, 2014 ) with six RCTs were used to compare tamsulosin plus tadalafil with tamsulosin alone in treating males with LUTS secondary to BPH ( Figure 1 ). The details of six articles and baseline characteristics of patients are listed in Tables 1 and 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%